The Development of A Reliability Evaluation Application for Power Plant Steam Turbine Vibrations to Predict Its Failure - Moch. Faqih; Nu Rhahida Arini; Hendrik Elvian Gayuh Prasetya (EMITTER International Journal of Engineering Technology, 2021)
A steam turbine is the most critical component in a thermal power plant. Due to its crucial function, it should be maintained to be able to operate without failure. This paper aims to develop an application that can be used to analyze the reliability and synchronization of vibrations in a single evaluation through the application. The application is helpful to decide the proper time the maintenance should be performed in order to provide a better maintenance strategy. In this paper, the application was used to make an ease in evaluating the reliability and vibration of a 670 MW power plant steam turbine. The reliability was analyzed by qualitative and quantitative methods. The vibration evaluation using Fast Fourier Transform (FFT) was done by diagnosing the failure symptoms from vibration spectrum. The analysis of synchronization of vibrations conducted by comparing the vibration frequency and the natural frequency of the system which can be calculated easily using the application. The algorithm program of both evaluations was built using GNU Octave software to make a friendly user interface. From the evaluation result, the most critical components of the steam turbine are coupling, labyrinth seals, bearing, diaphragm, turbine control valve, and turbine stop valve. The maintenance interval based on the expected reliability of 90% produces the highest reliability improvement. Based on the vibration analysis, there is no failure symptoms detected in the turbine bearings. Furthermore, the dominant frequencies of vibration are distant from the natural frequency. Therefore, the steam turbine condition is acceptable to operate.